Corporate Governance and Intellectual Capital: Impact on the Financial Performance of State-Owned Enterprises in Indonesia - Husnah Nur Laela Ermaya; Ayunita Ajengtiyas Saputri Mashuri (Syntax Corporation Indonesia, 2021)
Using company size and leverage as control variables, this study aims to evaluate the influence of institutional ownership, an independent board of commissioners, an audit committee, and intellectual capital on financial performance. The population in this study is all state-owned companies registered with the Ministry of SOEs with a period of observation for 4 years, namely in 2016-2019. Purposive sampling was used in this study to collect samples, and a total of 164 samples were collected. The data analysis methods utilized in this study include descriptive statistical tests, classic assumption tests, and hypothesis testing utilizing multiple regression analysis by SPSS 25 version. According to the findings of this study, institutional ownership and intellectual capital have a substantial beneficial influence on financial performance, whereas the independent commissioner has a large negative effect on financial performance and the audit committee has no effect on financial performance.